Traditional and “new” cardiovascular risk markers and factors in pediatric dialysis patients - Civilibal, Mahmut; Caliskan, Salim; Oflaz, Huseyin; Sever, Lale; Candan, Cengiz; Canpolat, Nur; Kasapcopur, Ozgur; Bugra, Zehra; Arisoy, Nil (Pediatric nephrology (Berlin, West), 2007)
Cardiovascular disease (CVD) is the principal cause of mortality in patients with end-stage renal disease (ESRD). The aim of this study was to analyze carotid intima-media thickness (cIMT), endothelium-dependent dilatation (EDD), and left ventricular mass index (LVMI) as the cardiovascular risk markers and to investigate the independent risk factors of these markers in pediatric dialysis patients. This study included 39 children and adolescents undergoing dialysis (15 hemodialysis and 24 peritoneal dialysis) and 15 age- and gender-matched healthy subjects. The cIMT and EDD were assessed by high-resolution ultrasound, and LVMI was calculated from standard echocardiographic measurements. Compared with control subjects, cIMT standard deviation scores (SDS), LVMI, total homocysteine (tHcy), and high-sensitivity C-reactive protein (hs-CRP) values were significantly higher in patients, but EDD values did not differ. The mean hs-CRP level was significantly higher in hemodialysis (HD) patients than in peritoneal dialysis (PD) patients. The cIMT-SDS and LVMI were associated with several variables in univariate analysis. Stepwise linear regression analysis, indexed SBP (p = 0.017), and hemoglobin (p = 0.001) turned out to be independent variables for predicting LVMI, and a significant predictor of cIMT was indexed diastolic blood pressure (DBP) (p = 0.035). The causes of atherosclerosis and left ventricular hypertrophy are multifactorial in children and adolescents with ESRD. Better management of hypertension and anemia may be priorities for preventing or improving CVD in these patients.